The risk of cardiac events in patients who received concomitant levofloxacin and amiodarone - Luigi Brunetti; Seung-Mi Lee; Ronald G. Nahass; David Suh; Benjamin Miao; John Bucek; Dongwon Kim; Ok-Kyu Kim; Dong-Churl Suh (International Journal of Infectious Diseases, 2019)
Objectives: Levofloxacin and amiodarone are both known to prolong the QT interval. This study was conducted to estimate the risk of cardiac events in patients receiving concomitant levofloxacin and amiodarone. Methods: The study included patients who were admitted to a large academic community medical center from 1/2012 to 12/2015 and received both levofloxacin and amiodarone at some point during their hospitalization. Patients received concomitant or non-concomitant levofloxacin and amiodarone during hospitalization. The primary outcome was the occurrence of cardiac events during therapy. The secondary outcome was the proportion of patients with an electrocardiogram performed before and after initiation of therapy. Odds ratios for cardiac events were calculated using a multivariable logistic regression model with and without adjusting for the study variables. The concomitant group was further evaluated for predictors of the primary outcome using multivariable logistic regression. Results: This study included 240 patients, 164 (68.3%) of whom received concomitant levofloxacin and amiodarone. Concomitant medication therapy was associated with a greater than six-fold increased risk of cardiac events after adjusting for the study variables (Odds Ratio = 6.20; 95% Confidence Interval = 1.34–28.62). Conclusions: Patients receiving concomitant amiodarone and levofloxacin experienced a five-fold increase in cardiac events compared to patients given either medication alone. Keywords: Levofloxacin, Amiodarone, Cardiac risk, Cardiac death, QT interval